2018
DOI: 10.1021/acsnano.8b03977
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 Memristors Exhibiting Variable Switching Characteristics toward Biorealistic Synaptic Emulation

Abstract: Memristors based on 2D layered materials could provide biorealistic ionic interactions and potentially enable construction of energy-efficient artificial neural networks capable of faithfully emulating neuronal interconnections in human brains. To build reliable 2D-material-based memristors suitable for constructing working neural networks, the memristive switching mechanisms in such memristors need to be systematically analyzed. Here, we present a study on the switching characteristics of the few-layer MoS me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
254
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(266 citation statements)
references
References 52 publications
11
254
0
1
Order By: Relevance
“…[131] Sangwan et al demonstrated gate-tunable multi-terminal memtransistor based on polycrystalline monolayer MoS 2 and explored the device application in neuromorphic computing. [131] Sangwan et al demonstrated gate-tunable multi-terminal memtransistor based on polycrystalline monolayer MoS 2 and explored the device application in neuromorphic computing.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[131] Sangwan et al demonstrated gate-tunable multi-terminal memtransistor based on polycrystalline monolayer MoS 2 and explored the device application in neuromorphic computing. [131] Sangwan et al demonstrated gate-tunable multi-terminal memtransistor based on polycrystalline monolayer MoS 2 and explored the device application in neuromorphic computing.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[50][51][52][53] Given the strong in-plane chemical bonds, manipulating the ion distribution in 2D chalcogenides by an electric field is initially thought to be unlikely. [50][51][52][53] Given the strong in-plane chemical bonds, manipulating the ion distribution in 2D chalcogenides by an electric field is initially thought to be unlikely.…”
Section: Anion-driven Rs Effectsmentioning
confidence: 99%
“…[50][51][52][53] Given the strong in-plane chemical bonds, manipulating the ion distribution in 2D chalcogenides by an electric field is initially thought to be unlikely. [53] Considering that sulfur www.advelectronicmat.de ions have a higher mobility than molybdenum ions, sulfur ions are more likely to redistribute during device programming, and sulfur vacancies can act as n-type dopants and modulate the Schottky barrier height at the electrode/MoS 2 interface that leads to the observed RS behaviors. For example, in a memristive device based on mechanically exfoliated MoS 2 (Figure 2i), it was found that applying 5000 strong programming pulses (20 V/2 ms) can lead to the modulation of the S:Mo atomic ratio, with an increased (decreased) atomic ratio near the anode (cathode) (Figure 2j,k).…”
Section: Anion-driven Rs Effectsmentioning
confidence: 99%
See 2 more Smart Citations